PENGARUH LINGKUNGAN SEKOLAH TERHADAP PEMBENTUKAN KARAKTER SISWA - Hariyanto, Alvitoni Putra (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
The school environment plays a very important role in character formation in children, where at school it is best to implement good habits and instill good behavior by creating teaching and learning activities that can stimulate children to become even better. Character education is a very important and strategic step to build national identity and encourage the formation of a new Indonesian society. Factors that influence student development are environmental factors. The environment plays an important role in the development of pre-adolescent children. The environment influences students at critical periods of their development. This impact is very visible in pre-adolescent children. According to Zubaedi (2013: 178), the factors that influence the success of character education are instincts/instincts that motivate you to do something, customs/habits that exist within oneself and the environment one lives in, heredity/heredity which influences the child's innate characteristics, and an environment that helps support character formation. This research uses a quantitative type of research with data collection from questionnaires, interviews, observations and documentation.